PENGEMBANGAN WISATA BAHARI DI PULAU TERLUAR BERBASIS KESESUAIAN LAHAN DAN DAYA DUKUNG (Studi Kasus Pulau Lingayan Sebagai Pulau Terluar di Kabupaten Tolitoli, Provinsi Sulawesi Tengah) - Gladys Peuru; Mennofatria Boer; Ismudi Muchsin; Yusli Wardiatno (Buletin PSP, 2012)
This research was conducted in Lingayan Island, Tolitoli Regency, center of Sulawesi Province, from January until December 2011. This research was aimed to analyze the suitability and carrying capacity of Lingayan Island Tolitoli Regency. The method used was survey method, analysis of  carrying capacity with Ecological Footprint Analysis and indepth interview. Marine tourism activities in Lingayan Island is suitable for diving (56.02 ha), snorkeling (121.67 ha) and beach tourism (13.18 ha). The ecology, physical and water carrying capacity of the island is 86 people/day, 2.5 ha and 1.7, repectively. The results show that the potential ecologically productive area of the island is  still enough to accommodate the number of coming tourists. Key word: carrying capacity, Lingayan Island, marine tourism